The Role of Retirement Wealth and Career Adaptability in Forming Attitudes on Retirement in Pontianak City Health Nurses - Sunardi Ginting (PT Mattawang Mediatama Solution, 2023)
This study aims to examine the strength of retirement wealth as a predictor variable for the formation of attitudes towards retirement and career adaptability as a mediation in the relationship between the two. The facts prove that a large part of the population perceives retirement negatively due to the inability to provide adequate retirement wealth. To overcome this condition, a mediating variable is needed, such as career adaptability, because this variable has succeeded in strengthening the positive attitude of workers in overcoming various obstacles and changes throughout their career, but their role has not been tested in forming attitudes towards retirement. To prove the truth of the four hypotheses proposed, researchers involved a sample of 257 respondents consisting of 185 women and 72 men. They are health nurses who work in various private hospitals in the city of Pontianak with an age range of 40 to. 59 years. Data collection was carried out using the snowball sampling technique and processed using WarpPls version 6 software. The results of data processing prove that retirement wealth and career adaptability are positive and significant predictor variables for the formation of a positive attitude towards retirement. If the strength of the role of the two variables is compared, then the role of career adaptability as a predictor variable is even greater than the role of retirement wealth in shaping attitudes towards retirement. For the career adaptability variable, apart from being a predictor variable it is also a positive and significant mediating variable in the role of retirement wealth in the formation of positive attitudes towards retirement. The researcher suggests that every worker should continue to increase their retirement wealth and career adaptability, because these two variables are proven to be important for establishing a positive attitude towards retirement. JEL: J26 Retirement • Retirement Policies